Evaluasi Penggunaan Ramipril dan Candesartan pada Pasien Rawat Inap COVID-19 dengan Komorbid Hipertensi di RSUD Dr. Moewardi - Azizah, Deva Yolanda Dwi Nur; Wijayanti, Tri; Cahyo, Lukito Mindi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Hypertension is the most common comorbid in patients infected by COVID-19. Drugs often given for the treatment of hypertension, namely ramipril, and candesartan, are thought to increase the development of COVID-19 because the angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARBs) increase the expression of ACE-2, which is the binding site of SARS-CoV-2. This study aims to analyze the effect of using ramipril and candesartan on healing in hospitalized patients with COVID-19 with hypertension at RSUD dr. Moewardi in 2020. This study was conducted retrospectively. The results were presented descriptively and used medical record data of hospitalized patients with COVID-19 with comorbid hypertension at RSUD dr. Moewardi in 2020. Using ramipril and candesartan affects patient recovery in terms of length of stay (LOS), symptom relief, and RT-PCR test results. Analysis of the research data using SPSS with Spearman correlation test. The Spearman correlation test showed that there was a fairly strong relationship between the use of ramipril and candesartan in patients with COVID-19 with comorbid hypertension on LOS, symptom relief, and RT-PCR test results. The study results show that using ramipril and candesartan can improve the recovery of patients with COVID-19 with comorbid hypertension. ACEI and ARB drugs have not been proven to worsen the patient's condition so their use can be continued.